2018
DOI: 10.1007/s40094-018-0288-x
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of energy lost by radiation and convection during laser welding of TA6V titanium alloy

Abstract: Laser welding is being used more frequently in industrial processes because of its advantages; therefore, energy loss in welding is an important issue during planning and operation. We calculated the energy losses expected during the laser welding of TA6V titanium alloy. We used the heat equation to describe the energy distribution of solid and liquid TA6V. The solid-to-liquid phase change was taken into account by comparing the accumulated energies and enthalpy of fusion. A numerical model was used to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…For the numerical calculations, mechanical and thermal parameters have been taken from [31]. The titanium alloy TA6V, commonly used in additive manufacturing, is considered and its properties are set in Table 3.2.1.…”
Section: The Thermoelastic Equilibrium System Readsmentioning
confidence: 99%
“…For the numerical calculations, mechanical and thermal parameters have been taken from [31]. The titanium alloy TA6V, commonly used in additive manufacturing, is considered and its properties are set in Table 3.2.1.…”
Section: The Thermoelastic Equilibrium System Readsmentioning
confidence: 99%
“…The FEA method requires calibration of the heat source parameters to get a solution with acceptable accuracy for predicting the transient temperature field in the heated products and melted pool geometry. The authors included the effect of convection and radiation into their transient temperature field modelling via FE boundary conditions as these effects are deem significant [23][24]. Usually, the FEA boundary conditions, imposed on the external surfaces of the spatial domain, using FEA packages such as ANSYS [14][15][16][17][18][25][26][27] or ABAQUS [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Lemkeddem et al [24] developed a numerical model to determine transient temperature distribution for the laser welding of two identical TA6V thin plates, taking account the energy lost by radiation and convection. They concluded that it is necessary to include energy losses in the welding area to improve laser welding efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation